A Prospective Study on The Utilization Pattern of Antibiotics and Assessing Its Dosage Appropriateness in Patients Undergoing Haemodialysis - Abnekalli, Sachin; Ramaiah, Balakeshwa; Prabhudev, Banjara Raju; Koju, Merit (Indian Journal of Pharmacy Practice)
Background: Antibiotic use is common in haemodialysis patients, increasing the risk of multidrug resistance and toxicity. Monitoring renal function and ensuring prescribing practices are essential to prevent adverse outcomes in renally ill patients. Materials and Methods: This prospective observational study was conducted by comparing patient antibiotic regimens to globally accepted guidelines, the primary outcome was to assess their dose appropriateness by collecting patients Serum creatinine levels to evaluate renal function by using Cockcroft-Gault formula, MDRD equation, and CKD-EPI equation. These three recognised strategies were used for determining the dosage appropriateness for antibiotics based on each patient’s creatinine clearance. Results: The study population was predominantly male (64.5%), with a mean age of 46.6 years in adults and 71.1 years in the elderly. Hypertension, diabetes, CKD, and other renal diseases were common, with sepsis and metabolic acidosis as key factors for initiating dialysis. A total of 126 antibiotics, mainly Meropenem and Piperacillin-tazobactam, were prescribed; 15 were inappropriately dosed, and only 8 antibiotics were prescribed which doesn’t require dose adjustments. The study showed improvement in post-HD serum creatinine compared to pre-HD serum creatinine (95% CI, 6.02±2.48 vs 5.01±1.94, p=0.0049). While 70.8% received appropriately dosed antimicrobials, 18.9% had inappropriate doses, emphasizing the need for improved dose optimization based on creatinine clearance. Conclusion: This study highlights the significant antibiotic exposure in haemodialysis patients, emphasizing the need for targeted interventions and antimicrobial stewardship to improve prescribing practices and patient safety.
Keywords: Antibiotics; Chronic kidney disease; Haemodialysis; Creatinine clearance; Renal dose adjustments